Aplikasi Findgo-ITATS Berbasis Android Dengan Algoritma SURF Untuk Menampilkan Informasi Lokasi Di ITATS - Hapsari, Rinci Kembang; Sulaiman, Nur; Hermanto, Luky Agus (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2016)
Institut Teknologi Adhi Tama Surabaya (ITATS) is an institute that has relatively wide territory and complicated building arrangement for outsiders especially related to identification of buildings that they want to visit. To overcome this problem, an android based application that can be used to gain information related to those buildings, locations of places or important places in real-time is required. Augmented Reality (AR) is the appropriate technology to display environment and locations information at ITATS in real-time. The implementation of Augmented Reality technology on android based smartphones using Speeded Up Robust Features (SURF) can identify pictures continuously and has proper identification speed. Speeded Up Robust Features (SURF) is an algorithm that has been commonly applied in correspondence matching because it is faster than Scale Invariant Feature Transform (SIFT) and has appropriate and accurate performance maintenance. In designing this application, there are three main stages that should be considered, namely: initialization, tracking marker, and object rendering. Initialization is the stage where images that becomes the database is preliminary processed with Speeded Up Robust Features (SURF) algorithm andÂ the preparation of the displayed information on the usersâ€™ smartphones. The second is tracking marker, smartphone camera takes pictures continuously while processing every inputted image applying Speeded Up Robust Features (SURF) and conducting matching process of images in the database. The final stage, after a match is found, this application displays the text information which corresponds with the matching result. The reliability of this system in recognizing locations at ITATS is 81.66% and average time required is 2.333 seconds.